Action Mode of Gut Motility, Fluid and Electrolyte Transport in Chronic Constipation - Zhao, Qi; Chen, Yan-Yan; Xu, Ding-Qiao; Yue, Shi-Jun; Fu, Rui-Jia; Yang, Jie; Xing, Li-Ming; Tang, Yu-Ping (Frontiers in Pharmacology, 2021)
Chronic constipation is a common gastrointestinal disorder, with a worldwide incidence of 14–30%. It negatively affects quality of life and is associated with a considerable economic burden. As a disease with multiple etiologies and risk factors, it is important to understand the pathophysiology of chronic constipation. The purpose of this review is to discuss latest findings on the roles of gut motility, fluid, and electrolyte transport that contribute to chronic constipation, and the main drugs available for treating patients. We conducted searches on PubMed and Google Scholar up to 9 February 2021. MeSH keywords “constipation”, “gastrointestinal motility”, “peristalsis”, “electrolytes”, “fluid”, “aquaporins”, and “medicine” were included. The reference lists of searched articles were reviewed to identify further eligible articles. Studies focusing on opioid-induced constipation, evaluation, and clinic management of constipation were excluded. The occurrence of constipation is inherently connected to disorders of gut motility as well as fluid and electrolyte transport, which involve the nervous system, endocrine signaling, the gastrointestinal microbiota, ion channels, and aquaporins. The mechanisms of action and application of the main drugs are summarized; a better understanding of ion channels and aquaporins may be helpful for new drug development. This review aims to provide a scientific basis that can guide future research on the etiology and treatment of constipation.